The representation of Islamic militants in Bangkok Post and The Nation / Angkana Warisri - Warisri, Angkana (2014)

(untitled)
This research report focuses on a Critical Discourse Analysis of the discursive strategies and related linguistic devices employed in the representation of Islamic militants in editorials and opinion editorials of the local mainstream newspapers. Regarding issues of the ongoing violence in the Muslim-dominated area of Southern Thailand, most researchers have conducted studies in the discipline of social science. On the other hand, a few studies pay attention to such an issue through an examination of the language use in the media reportage. Hence, this study points to a linguistic analysis of the construction of Muslim militants who are deemed as the real perpetrators of the southern disorder and other relevant social actors. The textual data consist of 28 editorials and opinion editorials collected over a period of seven months (April to December 2004 with the exception of June and July in which no acts of violence appeared), from the English language newspapers in Thailand, namely The Nation and Bangkok Post. Wodak‟s Discourse-Historical Approach (Wodak et al., 1999; Wodak, 2001; and Reisigl and Wodak, 2009) is adopted as a framework to examine the discursive construction of the positive self- presentation and negative other-presentation of Islamic militant and related social actors in the editorials discourses. Findings show that self-attributions of superiority and other- attributions of inferiority by the news media through the referential, predicational and argumentative strategies create the strong impacts on the stereotypical perception of the text receivers. In this respect, the negative portrayal of Islamic militant social actor as a threat to national security reinforces the racial and religious prejudices against not only Muslims but the religion of Islam as well among the readers.